Improvements in Medical System Safety Analytics for Authentic Measure of Vital Signs Using Fault-Tolerant Design Approach - Lakkamraju, Prasadraju; Anumukonda, Madhu; Chowdhury, Shubhajit Roy (Frontiers in Medical Technology, 2021)
The paper presents a novel design method to improve the system availability using fault-tolerant features in a non-invasive medical diagnostic system. This approach addresses the effective detection of functional faults, improves the un-interruptible system operating period with reduced false alarms, and provides the authentic measure of vital cardiac signs by using diverse multimodal sensing elements like photoplethysmogram (PPG) and electrocardiogram (ECG). In existing practice, most systems relied on a 1oo1(One-out-of-One) design method, which has inherently limited accuracy. In this proposed approach, the quality of segregated authentic vital sign measured values could tremendously benefit in performing resourceful nursing with negligible alarm fatigue and leads to predicting the illness more accurately. The System builds upon the selected 2oo2 (two-out-of-two) safety-related design architecture and evaluated with implemented functions like fault detection and identification logic, correlation coefficient-based safety function, fault-tolerant safe degradation switching mechanism for accurate measurements. The System tested on fifty adults of various age groups, and the data analysis shows that achieved a high accurate vital sign data in this fault-tolerant approach with reduced false alarms. The proposed design method evaluated safety-related mechanisms along with a combination of same and diverse sensors in a medical monitoring device shows more reliable functioning of the System and authentic data for better nursing. This design approach shows improvement from 45% to 55% in system availability and allows for accurate, and uninterruptable tracking of vital signs for better nursing at critical times in ICU.